STRATEGI PENGEMBANGAN INDUSTRI KREATIF DIGITAL MELALUI KOMPETISI DAN KOLABORASI - IDA BAGUS KETUT ALAMSYAH (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2026)
The digital creative industry is a strategic sector in supporting the transformation of the knowledge-based economy. The animation subsector has great potential in creating added economic value as well as being an effective public communication medium. Central Java's human resource potential reaches 10,000 graduates each year from content majors from vocational schools and universities, thus requiring facilitation and appreciation in their work. This article describes the Animation and Creative Video Competition program in Central Java Province and formulates a strategy to strengthen the digital creative industry ecosystem based on competition and collaboration. The research uses a descriptive qualitative approach based on program evaluation with document analysis and activity best practices. The results of the study indicate that the animation competition program is effective as a talent identification mechanism (talent discovery), and has advantages in integrating works as a medium for public policy communication through screenings in cinemas and videotrons. This program also demonstrates innovation in providing ongoing appreciation to winners by utilizing animated works as a public campaign medium for the Regional Office of Customs and Excise in eradicating illegal cigarettes, which are shown in cinema networks and outdoor media (billboards/videotrons). This form of appreciation provides wider exposure space for creators while increasing the social and economic value of digital creative works. These findings are expected to serve as a policy reference for local governments in developing a sustainable digital creative industry